STRICT FORMALISM OF WILLS OR SOVEREIGNTY OF TESTAMENTARY INTENT: WHICH SHOULD PREVAIL? - Krstić, Novak (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The paper examines the tension between strict formalism and testamentary intent in the law of wills. Traditionally wills are strictly formal acts (forms ad solemnitatem): any deviation, even minor, renders the will invalid and triggers intestacy. Against this backdrop, Anglo-American theory and practice have advanced flexible approaches that prioritize testamentary intent over strict compliance, chiefly the harmless error doctrine and the dispensing power doctrine. These have influenced legislation and case law in common-law jurisdictions and spurred debate in continental European theory over whether priority should be given to strict formalism or to testamentary intent. The development of digital technologies further complicates the issue because electronic wills are not regulated, creating a real risk that such wills will be annulled despite the existence of clear testamentary intent. The paper cautions, however, against an overly liberal model, especially broad dispensing powers, which can erode the protective and evidentiary functions of form. Form still matters: it deters fraud, structures deliberation, and provides reliable proof. The author proposes a middle path: preserve essential formal elements that serve these functions, but allow courts, in favorem testamenti, to excuse minor defects when testamentary intent is proven. Such flexibility would better honor decedents’ last wishes without sacrificing core safeguards, and it would create doctrinal space to validate technology-assisted wills even before comprehensive legislation on electronic wills is enacted.
Keywords: testament; form; testamentary intent; last will; voidability